EFEKTIFITAS SUSU KEDELAI TERHADAP PENURUNAN GEJALA HOT FLUSH PADA WANITA KLIMAKTERIUM - Hetty Maria Sihotang (STIKes Mitra Husada Medan, 2018)
The end of the menstrual period (menopause) is often accompanied by a number of symptoms, such as hot flashes, night sweats, fatigue, insomnia, depression, anxiety, memory disorders, urogenital symptoms, and often causes impaired quality of life. Of all these symptoms, hot flashes are reported as one of the most disturbing symptoms that affect up to 80% of women. In women who produce less estrogen, isoflavones (phytoestrogens) can produce enough estrogen activity to overcome symptoms due to menopause, such as hot flashes, one of which is sourced from soybeans. The purpose of this study was to determine the effect of soy milk on the reduction of hot flush symptoms in climacterial women. This study used a quasi-experimental method with the One Group Pretest-Postest design of 30 climacterial women, who met the inclusion and exclusion criteria were given soy milk 100 mg/day (90 days). The bivariate analysis used in this study is a non-parametric difference test with the Wilcoxon test. The results of bivariate analysis by comparing the pre and posttest values showed the value of ρ = 0.001 (ρ <0.05). The conclusion is that giving soy milk affects the reduction of hot flush symptoms in climacteric women. Keywords: Soya Milk, Reduction, Hot Flush